Nomenclatural clarification of the names Pelargonium althaeoides and P. chamaedrifolium (Geraniaceae) - Roux, M. Marianne Le; Klopper, Ronell R. (Phytotaxa, 2020)
While revising the southern African species of Pelargonium L’Hér. in Aiton (1789a: 417) sect. Peristera De Candolle (1824: 654) (Le Roux 2019), it was found that two names are in circulation for a single species. This matter was not addressed in the revision by Le Roux (2019) as P. althaeoides (Linnaeus 1753: 679) L’Hér. in Aiton (1789a: 420) was moved from Pelargonium sect. Peristera [subgen. Parvulipetalum Röschenbl. & F.Albers in Röschenbleck et al. (2014: 57)] to section Campylia (Lindl. ex Sweet 1820: pl. 43) De Candolle (1824: 656) (subgen. Pelargonium) in a molecular study by Röschenbleck et al. (2014). The matter therefore requires clarification.